FREQUENCY OF QTc PROLONGATION IN PATIENTS WITH HEMORRHAGIC STROKE - Malik, Sarwar; Sattar, Rukhsana Abdul; Shah, Shahnaz; Rehman, Hisala; Tahira, Tahira; Ismail, Muhammad Ali (Journal of Ayub Medical College Abbottabad, 2013)
Jinnah Postgraduate Medical Centre, Karachi, Pakistan Background: Acute cerebral events play an important role in generating autonomic imbalance especially cardiac rhythm disturbances. This forms the basis of significant lethal abnormalities of heart rate and rhythm like QTc prolongation, ventricular fibrillation, asystole, and ultimately death. This study was conducted to determine the frequency of QTc prolongation in patients presenting with acute haemorrhagic stroke at a tertiary care hospital. Methods: This descriptive case series was conducted at Medical Unit-I, ward-5, Jinnah Postgraduate Medical Centre (JPMC), Karachi, from 13 October, 2009 to 12 April, 2010. Patients of either gender and age >18 years who presented within 48 hours of onset of acute hemorrhagic stroke for the first time, confirmed by computerized tomography (CT) scan of brain were included. A 12 lead electrocardiogram (ECG) was performed. Lead III and VI were used for this due to their importance in this aspect. QTc was then calculated by using Bazetts formula. Data was analysed using SPSS-12. Results: Among 95 patients of acute haemorrhagic stroke, 48 (50.5%) had prolonged QTc in lead III, 47 (49.5%) had prolonged QTc in lead VI. The average QTc interval in lead III was 440.4±45.2 (Range=364-571). Proportion of prolonged QTc in lead III was higher in males than females. Frequency of QTc III prolongation was higher in comparatively younger age groups than older age groups. Conclusion: The frequency of prolonged QTc interval among patients of acute hemorrhagic stroke is alarmingly higher in our setup. Prolonged QTc is a useful predictor of impending clinical deterioration and provide an opportunity for early intervention to reduce severe loss like mortality. Keywords: Haemorrhagic stroke, QTc prolongation